2023
DOI: 10.1002/lary.31157
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Patients Living with Retrograde Cricopharyngeal Dysfunction

Mattea E. Miller,
Ioan Lina,
Karla O'Dell
et al.

Abstract: ObjectivesRetrograde cricopharyngeal dysfunction (RCPD) is a newly described condition resulting from failure of cricopharyngeal sphincter relaxation during periods of esophageal distension that results in the inability to burp. Patients' perspectives on symptom experiences, barriers to care, and treatment benefits were investigated.Study DesignQualitative semi‐structured interviews were conducted with patients diagnosed with RCPD who had been treated with botulinum toxin injection into the cricopharyngeus mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…People living with RCPD often report never being able to burp with bothersome symptoms starting in adolescence that continue to worsen into adulthood [5]. Qualitative interviews conducted with patients living with RCPD revealed that patients with RCPD are most affected by symptoms of bloating and gurgling noises, which cause increased anxiety, social isolation, and decreased productivity (days absent from work and/or school) [24]. In search of reprieve, patients make lifestyle modifications, change their exercise regimen, limit or modify their diet, and try remedies posted on online forums such as 'air vomiting' (self-inducing vomiting to release trapped air in the stomach) in efforts to minimize their symptoms [24].…”
Section: Lived Experience Of Rcpdmentioning
confidence: 99%
See 2 more Smart Citations
“…People living with RCPD often report never being able to burp with bothersome symptoms starting in adolescence that continue to worsen into adulthood [5]. Qualitative interviews conducted with patients living with RCPD revealed that patients with RCPD are most affected by symptoms of bloating and gurgling noises, which cause increased anxiety, social isolation, and decreased productivity (days absent from work and/or school) [24]. In search of reprieve, patients make lifestyle modifications, change their exercise regimen, limit or modify their diet, and try remedies posted on online forums such as 'air vomiting' (self-inducing vomiting to release trapped air in the stomach) in efforts to minimize their symptoms [24].…”
Section: Lived Experience Of Rcpdmentioning
confidence: 99%
“…Members sharing their symptoms and experiences living with RCPD provide detailed accounts of how to 'air vomit' (self-induced vomiting with the goal of allowing trapped air in the stomach out), their diagnosis of RCPD, and their experiences with botulinum toxin treatment. Participants report bringing information they found online to their physicians to facilitate a medical diagnosis of RCPD [24]. Referrals to specific physicians treating RCPD can also be found via social media, with many otolaryngologists being named on social media sites as providing botulinum toxin injections to treat RCPD [8,24,42].…”
Section: The Role Of Social Mediamentioning
confidence: 99%
See 1 more Smart Citation